Yours : a collection of CAPCO 2001. - Heyvaert, Rob; Swinnen, Johan (Frankfurt am Main CAPCO The Capital Markets Company, 2001)
Bailey, Robert ; Usle, Silvia ; Nickles, Nina ; Kaye, Marieka ; De Belder, Thérèse ; Tan, David ; Vidler, Muir ; Deegan, Shane ; Redgrave, Bianca ; Schoenberg, Dennis ; Broekaert, Elisabeth ; Wauman, Wim ; Geissler, Jeff ; Göthage, Mikael ; Shapiro, Carla ; Dockx, Nico ; Siekmeier, Christian ; Kondo, Hidenori ; Niemant, Caroline ; Holleben, Jan von ; Solesbury, Rebecca ; Chacaxiro, Dan ; Nybo, Torstein ; De Gendt, Greet ; Kochanek, Senta ; Buesing, Nina ; Pogorzaly, Marzena ; Miah, Riad ; Lang Maher, Amanda ; Rose, Marcus ; Finley, Rebecca ; Valerio, Geraldo ; Foo, Eric Christopher ; Geo, Daniella ; Peeters, Myriam ; Benhelima, Charif ; Soon-Choel Byun ; van Dort, Thierry ; Henry, Alison ; Beelen, Griet ; Barlois, Marie ; Aerts, Layla ; Puttmann, Jeanne ; Jibilian, Aram ; De Backer, Chris
Catalogus 2: Yours :a collection of CAPCO 2001, 130 p. : ill.: Fifty young, talented artists, who have studied art and photography all over the world, were asked to photograph the partners of the ambitious company Capco.
Engels
boek